Functional heterogeneity of calretinin‐expressing neurons in the mouse superficial dorsal horn: implications for spinal pain processing. (27th August 2015) - Smith, K. M.; Boyle, K. A.; Madden, J. F.; Dickinson, S. A.; Jobling, P.; Callister, R. J.; Hughes, D. I.; Graham, B. A.
Abstract : Key points: The superficial spinal dorsal horn contains a heterogeneous population of neurons that process sensory inputs. Information on the properties of excitatory interneurons in this region is limited. As calretinin is a protein thought to be restricted to an excitatory population in this region, the aim of this study was to characterize calretinin‐expressing neurons. Most calretinin cells (85%) exhibited large A‐type potassium currents and delayed firing action potential discharge, and received strong excitatory synaptic input, whereas the remainder exhibited hyperpolarization‐activated cation currents and low threshold T‐type calcium currents, and tonic‐ or initial bursting firing patterns, and received weak excitatory synaptic input. These respective features are consistent with properties of excitatory and inhibitory interneuron populations in this region of the spinal cord. Our findings have resolved a previously unidentified population of inhibitory interneurons. Furthermore, the contrasting excitability patterns of excitatory and inhibitory calretinin‐expressing neurons suggest that they play distinct roles in spinal sensory processing circuits. Abstract: Neurons in the superficial dorsal horn (SDH) of the spinal cord play an important role in nociceptive, thermal, itch and light touch sensations. Excitatory interneurons comprise ∼65% of all SDH neurons but surprisingly few studies have investigated their role in spinal sensory processing. Here we use a transgenic mouse to study putative excitatory SDH neurons that express the calcium binding protein calretinin (CR). Our immunocytochemical, morphological and electrophysiological analysis identified two distinct populations of CR‐expressing neurons, which we termed 'Typical' and 'Atypical'. Typical CR‐expressing neurons comprised ∼85% of the population and exhibited characteristic excitatory interneuron properties including delayed firing discharge, large rapid A‐type potassium currents, and central, radial or vertical cell morphologies. Atypical neurons exhibited properties consistent with inhibitory interneurons, including tonic firing or initial bursting discharge, I h currents, and islet cell morphology. Although both Typical and Atypical CR‐expressing neurons responded to noxious peripheral stimulation, the excitatory drive onto Typical CR‐expressing neurons was much stronger. Furthermore, Atypical CR‐expressing cells comprise at least two functionally distinct subpopulations based on their responsiveness to noxious peripheral stimulation and neurochemical profile. Together our data suggest CR expression is not restricted to excitatory neurons in the SDH. Under normal conditions, the contribution of 'Typical' excitatory CR‐expressing neurons to overall SDH excitability may be limited by the presence of A‐type potassium currents, which limit the effectiveness of their strong excitatory input. Their contribution may, however, be increased in pathological situations where A‐type potassium currents are decreased. By contrast, 'Atypical' inhibitory neurons with their excitable phenotype but weak excitatory input may be more easily recruited during increased peripheral stimulation. Abstract :